Morbidity, mortality and clinico-laboratory profile of COVID-19 related illness in children: a retrospective observational study from a tertiary care centre in India - Patra, Bijoy; Nimesh, Manju; Kaur, Parasdeep; Patil, Sumantha; Gupta, Hema; Jilowa, Saria; Bahl, Dheeraj (International Journal of Research in Medical Sciences, 2021)
Background: As India is poised for a third wave of SARS Co-V2 infection with a large unvaccinated pediatric population, it becomes imperative and pertinent for a study to find out its demographic, clinico-laboratory profile, and outcome in children with COVID-19 disease and its related illness. Methods: This is a retrospective observational study undertaken for Children and Adolescent admitted in the department of pediatrics of a teaching and tertiary care referral hospital, Delhi. Results: The median age of admitted children with COVID-19 disease was 11 years with an interquartile range 3 to 16 years. The median duration of hospital stay was 10 days (mean: 18±14 days). Mortality was 9/62 (14%). Recovery in non-severe (asymptomatic, mild, moderate) was 41/41 (100%), and in severe and critical illness including MISC was 42.8% (9/21). Mortality in severe and critical patients managed in SARI and COVID ward was 44% (8/18). Death among MISC patient in PICU was 33% (1/3). Difference in CRP rise was significant in severe and non-severe group of COVID-19 (p=0.017). Conclusions: Even though the morbidity and mortality associated with COVID-19 infection and related illness seems to be miniscule, the infection causes significant illness in the subgroup of children who requires hospitalization and can be fatal in those with comorbidity.